Frequency of Hepatitis B, C and HIV infections among transfusion-dependent Thalassemia patients in Bangladesh - Amatullah, Jumanah (BRAC Univeristy, 2018)
This thesis is submitted in partial fulfilment of the requirements for the degree of Bachelor of Science in Biotechnology, 2018.